SERANGAN HAMA PENGGEREK BATANG SEBAGAI INDIKATOR PEMBENTUKAN GUBAL GAHARU PADA POHON Gyrinops verstegii DI KAMPUNG SUSWENI - , AMILDA AURI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Gaharu is an aromatic substance with high economic value. Gaharu formation is caused by pathogenesis process that is started with wound stimulation on stem, branch or twig and other physical factor. One of factors causing physical damage is insect. This research was intended to (1) identify type of stem borer pest insect in gaharu tree (Gyrinops verstegii), area of attack and intensity of severity on polyculture land and (2) to identify role of stem borer pest attach as indicator of gaharu formation in Gyrinops verstegii tree. Method used was census method to identify all plant species in people mix garden. Then, identification was done to identify type of stem borer insect on gaharu tree. Then, Volatile Organic Component (VOC) analysis with GCMS was done to identify association between damage caused by insect and forming aromatic compound. Statistical analysis used in this research is regression analysis to determine association form. The results indicated that insect Megopis sp. (Cerambycidae) is found. Area of attacked and intensity severity of Megopis sp. infestation occur in more than 11 cm diameter. The highest attack area occurred in 10 and 7 year old trees (50% and 100%, respectively) and Intensity of severity are 70% and 62.2%. Result of GCMS indicated that there are compound 2-(2-phenylethyl) Chromen-4-one that is a compound forming aroma in gaharu. Regression analysis on damage level and chromone derivative compound forming indicated strong correlation with r2=0.509 and r = 0,713.